Tuning of strain and surface roughness of porous silicon layers for higher-quality seeds for epitaxial growth - Karim, Marwa (Springer, 2014)
Sintered porous silicon is a well-known seed for homo-epitaxy that enables fabricating transferrable monocrystalline foils. The crystalline quality of these foils depends on the surface roughness and the strain of this porous seed, which should both be minimized. In order to provide guidelines for an optimum foil growth, we present a systematic investigation of the impact of the thickness of this seed and of its sintering time prior to epitaxial growth on strain and surface roughness. Strain and surface roughness were monitored in monolayers and double layers with different porosities as a function of seed thickness and of sintering time by high-resolution X-ray diffraction and profilometry, respectively. Unexpectedly, we found that strain in double and monolayers evolves in opposite ways with respect to layer thickness. This suggests that an interaction between layers in multiple stacks is to be considered. We also found that if higher seed thickness and longer annealing time are to be preferred to minimize the strain in double layers, the opposite is required to achieve smoother layers. The impact of these two parameters may be explained by considering the morphological evolution of the pores upon sintering and, in particular, the disappearance of interconnections between the porous seed and the bulk as well as the enlargement of pores near the surface. An optimum epitaxial growth hence calls for a trade-off in seed thickness and annealing time, between minimum-strained layers and rougher surfaces. PACS CODES: 81.40.-z Treatment of materials and its effects on microstructure, nanostructure, and properties; 81.05.Rm Porous materials; granular materials; 82.80.Ej X-ray, Mössbauer and other γ-ray spectroscopic analysis methods